The effects of increasing heat waves on outpatient caregivers - Attitudes, measures and outlook - Frantzen, Chiara; Kaifie, Andrea (Journal of Occupational and Environmental Medicine, 2025)
Objectives Increasing heatwaves pose a significant health risk. This study investigates the impact of heatwaves on staff in outpatient care services in a large city in western Germany. Methods A cross-sectional survey was conducted from March to June 2023, which targeted the managers of 78 outpatient nursing services. The 33-item questionnaire addressed attitudes toward climate change, health impacts on patients and staff, and potential measures to improve working conditions during heatwaves. Results Of the 40 services that participated, 90% had not received training on climate adaptation; 38% felt uninformed about heat-related measures; and 50% requested more time for caregiving duties during heatwaves. Guidelines for heatwaves were supported by 78% of participants, and 75% wanted more heat-protection training. Conclusion Outpatient care services require more active involvement in heat-protection planning to safeguard staff as heatwaves become more frequent.
CRIS-Team Scopus Importer:2025-04-11
Keywords: climate change; healthcare adaptation; occupational groups; outpatient care; perception